Conceptualization of a Collaborative Decision Making for Flood Disaster Management - Zubir, Siti Nur Aishah; Thiruchelvam, Sivadass; Mustapha, Kamal Nasharuddin; Che Muda, Zakaria; Ghazali, Azrul; Hakimie, Hazlinda; Abdul Razak, Normy Norfiza; Mat Isa, Abdul Aziz; Hasini, Hasril; Mohamed Sahari, Khairul Salleh; Mat Husin, Norhayati; Rusli, Mohd Ezanee; et al. (Institute of Physics Publishing, 2016)
Flooding is the utmost major natural hazard in Malaysia in terms of populations affected, frequency, area extent, flood duration and social economic damage. The recent flood devastation towards the end of 2014 witnessed almost 250,000 people being displaced from eight states in Peninsular Malaysia. The affected victims required evacuation within a short period of time to the designated evacuation centres. An effective and efficient flood disaster management would assure non-futile efforts for life-saving. Effective flood disaster management requires collective and cooperative emergency teamwork from various government agencies. Intergovernmental collaborations among government agencies at different levels have become part of flood disaster management due to the need for sharing resources and coordinating efforts. Collaborative decision making during disaster is an integral element in providing prompt and effective response for evacuating the victims.